2020
DOI: 10.1523/jneurosci.1906-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The VLPFC versus the DLPFC in Downregulating Social Pain Using Reappraisal and Distraction Strategies

Abstract: The dorsolateral prefrontal cortex (DLPFC) and ventrolateral PFC (VLPFC) are both crucial structures involved in voluntary emotional regulation. However, it remains unclear whether the functions of these two cortical regions that are involved in emotional regulation, which are usually active in non-social situations, could be generalized to the regulation of social pain as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 83 publications
7
95
0
3
Order By: Relevance
“…Participants living in higher ADI areas had greater bilateral anterior insula connectivity with the vlPFC, a section of the PFC thought to underlie affect appraisal and emotion regulation ( Benelli et al, 2012 ; Prater et al, 2013 ; Zhao et al, 2021 ). Both the anterior insula and vlPFC are key nodes in the emotional salience network, an intrinsic connectivity network that is present during rest and anti-correlated with the default mode network ( Chai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants living in higher ADI areas had greater bilateral anterior insula connectivity with the vlPFC, a section of the PFC thought to underlie affect appraisal and emotion regulation ( Benelli et al, 2012 ; Prater et al, 2013 ; Zhao et al, 2021 ). Both the anterior insula and vlPFC are key nodes in the emotional salience network, an intrinsic connectivity network that is present during rest and anti-correlated with the default mode network ( Chai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These comparisons, however, did not encompass direct comparison within studies and failed to show a statistically significant difference. The causal role of the vlPFC in specific is supported by experimental TMS studies that demonstrated a facilitation of reappraisal after vlPFC stimulation (48,49). In a similar vein, transcranial direct current stimulation (tDCS) of the vlPFC may influence emotion regulation.…”
Section: Introductionmentioning
confidence: 98%
“…26 volunteers participated in the study (mean age 25.4, SD 3.5; 15 females, 10 males, 1 other gender). A similar sample size was used in previous studies that investigated the effect of TMS stimulation on emotion regulation 29 . Data from two subjects were discarded due to technical malfunctions during recording.…”
Section: Participantsmentioning
confidence: 99%
“…Only VLPFC stimulation resulted in a decrease of self-reported negativity of reappraised emotional pictures along with changes in cardiac reactivity measured by interbeat interval (IBI). In another experiment, the right DLPFC and VLPFC regions were stimulated using an offline 10Hz excitatory repetitive TMS (rTMS) protocol before participants were asked to use reappraisal to down-regulate their emotional responses to affective social stimuli 29 . The modulatory effects were quantified using the late positive potential (LPP; an ERP marker of the depth of emotional responses) and self-report scores.…”
Section: Introductionmentioning
confidence: 99%